Mentoring the Importance of Financial Literacy and Digital Literacy in the Welding Workshop Business - Afian, Affan; Mustikowati, Rita Indah; Sari, Ati Retna; Halim, Dimas Maulana; Khoir, Nadila Ulul (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The purpose of this activity is to increase the independence of partners through strengthening financial management and increase knowledge for partners about digitalization. By understanding the importance of good financial management and adopting the right technology, welding workshops can increase their competitiveness, improve operational efficiency, and improve the quality of their work. Method: The method developed was counseling, training and mentoring on financial literacy and digital literacy. In this activity, the importance of financial literacy and digital literacy is explained, as well as the benefits obtained in financial management and the application of digitalization. Practical Applications: financial literacy and digital literacy training helps improve the competitiveness of welding workshops in the market. Better performance, rapid technology adaptation, and better decisions, they can grow sustainably and expand their business reach. And maintain competitiveness in an ever-evolving and changing business environment. Conclusion: The combination of financial literacy and digital literacy gives welders a competitive advantage in a constantly evolving market, allowing them to adapt to change